USING JAZZ CHANTS IN TEACHING ENGLISH SPEAKING FOR YOUNG LEARNERS - Yani Awalia Indah; Aprilia Dwi Putri (ENGLISH, 2016)
Teaching English for Young Learners (TEYL), especially teaching English speaking is not easy. The teachers have to deal with the young learners who have the different characteristics with adult. Speaking is also the other problems for young learners. They feel hard to speak up. Knowing the characteristics and factors that cause difficulty in speaking for young learners, the teachers have to poses creative and effective method to teach English for young learners. One of the methods for teaching English speaking for young learners is jazz chant. This research employed Classroom Action Research to know the improvement of student English speaking skill using jazz chants. From the test, it showed that the average of all aspect; fluency, accuracy, pronunciation and intonation in every meeting, in each cycle had improved. The result of the observation also showed that there were improvement of students? participations and students? attitudes in every cycle.